2014
DOI: 10.1159/000362993
|View full text |Cite
|
Sign up to set email alerts
|

HDL-Bound Sphingosine 1-Phosphate (S1P) Predicts the Severity of Coronary Artery Atherosclerosis

Abstract: Background: We have recently demonstrated a reduction in HDL-bound sphingosine 1-phosphate (S1P) in patients with stable coronary artery disease (CAD). In the current study, we tested whether HDL-associated S1P is predictive for the degree of coronary stenosis, restenosis and overall CAD severity on follow up in patients undergoing elective percutaneous coronary intervention (PCI). Methods: Coronary angiography of patients with CAD (n=59) undergoing elective PCI and presenting for a follow up after 6 months (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 28 publications
1
47
0
3
Order By: Relevance
“…108 Although a crosssectional analysis in patients with CAD showed that patients who possessed HDL-S1P levels in the lowest quartile were more likely to demonstrate in-stent restenosis than patients in the higher quartiles, 118 the amount of HDL-associated S1P was not predictive for the development of restenosis during follow-up in CAD patients after percutaneous coronary intervention. 117 Additional findings of studies on HDL isolated from acute myocardial infarction patients suggest that a reduced S1P content of HDL impairs the capacities to stimulate endothelial nitric oxide production 119 and to inhibit endothelial apoptosis. 89 Moreover, a reduced HDL-associated S1P content has been related to defects in S1P-dependent activation of ERK1/2 and Akt signaling pathways as well as eNOS phosphorylation at Ser1177 in vascular endothelial cells in patients with CAD.…”
Section: Sphingolipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…108 Although a crosssectional analysis in patients with CAD showed that patients who possessed HDL-S1P levels in the lowest quartile were more likely to demonstrate in-stent restenosis than patients in the higher quartiles, 118 the amount of HDL-associated S1P was not predictive for the development of restenosis during follow-up in CAD patients after percutaneous coronary intervention. 117 Additional findings of studies on HDL isolated from acute myocardial infarction patients suggest that a reduced S1P content of HDL impairs the capacities to stimulate endothelial nitric oxide production 119 and to inhibit endothelial apoptosis. 89 Moreover, a reduced HDL-associated S1P content has been related to defects in S1P-dependent activation of ERK1/2 and Akt signaling pathways as well as eNOS phosphorylation at Ser1177 in vascular endothelial cells in patients with CAD.…”
Section: Sphingolipidsmentioning
confidence: 99%
“…115 In agreement with these data, in patients presenting with stable CAD, HDL-bound plasma S1P levels decreased depending on the number of vessels affected by the disease. 117 In a nested case control study involving 204 subjects stratified by HDL-cholesterol from the Copenhagen City Heart Study, S1P levels in the HDL-containing fraction of serum (depleted of apoB-containing lipoproteins) were inversely associated with the occurrence of ischemic heart disease. 108 Although a crosssectional analysis in patients with CAD showed that patients who possessed HDL-S1P levels in the lowest quartile were more likely to demonstrate in-stent restenosis than patients in the higher quartiles, 118 the amount of HDL-associated S1P was not predictive for the development of restenosis during follow-up in CAD patients after percutaneous coronary intervention.…”
Section: Sphingolipidsmentioning
confidence: 99%
“…According to Deutschman et al [15] the serum level of total S1P increases with advancement of the disease. The latter was not confirmed by Sattler et al [17]. The plasma level of ceramide in patients with coronary heart disease was reduced in one work [13] and elevated in another study [15].…”
Section: Discussionmentioning
confidence: 75%
“…Sattler et al [16] found reduction in the total plasma HDL-bound S1P and elevation in the level of non-HDL bound S1P in patients with stable coronary heart disease and after myocardial infarction. Further work of the authors [17] revealed that the level of HDL-bound S1P remained stable with the advancement of the disease. It was previously reported that myocardial infarction in humans affects metabolism of bioactive sphingolipids not only in plasma but also in erythrocytes and platelets.…”
Section: Introductionmentioning
confidence: 92%
“…Акти-вация синтеза NO включает связь ЛПВП с SR-B1, который акти-вирует фосфатидилинозитол-3-киназу (PI3K)/Akt (RAC-α-серин/треониновая протеинкиназа) сигнального пути и запуска-ет фосфорилирование эндотелиальной NO-синтазы (eNOS); эта активация также зависит от рецепторов С1Ф [59][60][61]. Благодаря тому что С1Ф обогащает ЛПВП3, этот подкласс ЛПВП может иметь решающее значение для зависимой от ЛПВП вазодилата-ции [28,62].…”
Section: терапевтический архив 9 2016unclassified